2013
DOI: 10.1016/j.diii.2013.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergency ultrasound: A prospective study on sufficient adequate training for military doctors

Abstract: "Accelerated" training for generalist military doctors in front line ultrasound is achievable. The recommended number of 25 ultrasounds per target is not appropriate for all ultrasound targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…no pediatric or women's health departments. Nevertheless, in hospitals with pediatric or women's health departments, ultrasonography is often performed by pediatricians or gynecologists and not radiologists, thus supporting the idea of training clinicians in other medical specialties [20]. In addition, the absence in our hospital of a department of urology might have led to an over-estimation of what were considered to be urgent requests for testicular ultrasonographic examinations (eight out of the 24 requests considered as urgent in our study) since suspected cord torsion is an indication for immediate surgery and other indications for urgent exploration of the scrotum being limited.…”
Section: Discussionmentioning
confidence: 98%
“…no pediatric or women's health departments. Nevertheless, in hospitals with pediatric or women's health departments, ultrasonography is often performed by pediatricians or gynecologists and not radiologists, thus supporting the idea of training clinicians in other medical specialties [20]. In addition, the absence in our hospital of a department of urology might have led to an over-estimation of what were considered to be urgent requests for testicular ultrasonographic examinations (eight out of the 24 requests considered as urgent in our study) since suspected cord torsion is an indication for immediate surgery and other indications for urgent exploration of the scrotum being limited.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have found PHUS training to be feasible both with physicians [54,55] and non-physicians [53,[56][57][58][59][60]. Nonphysician use of PHUS in changing patient management has not been studied.…”
Section: Summary Of Evidencementioning
confidence: 94%
“…Among five urgent US targets (FAST, pleura, bladder, abdominal aorta, and gallbladder), gallbladder US is the most difficult to perform [14]. Previous studies have shown that emergency department bedside ultrasonography (EUS) performed by EPs had a good agreement with the radiologists in detecting cholelithiasis; however, the EPs in these studies had varying degrees of experience [15,16].…”
Section: Biliary Diseasementioning
confidence: 96%
“…In addition, aortic US is the fastest investigation to perform [14]. A pilot study investigated primary-care residents (PCRs) who performed US screening for abdominal aortic aneurysm, and showed that PCRs with no US experience who after receiving little formal US training were able to rapidly learn the technique of US imaging of the aorta with only five to 10 patient examinations [24].…”
Section: Abdominal Aortic Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation